Origami Exploration: Preschool Learning Management In Developing Children's Fine Motor Abilities - Nining Muslehud Agustin; Finadatul Wahidah (LP3M KH Yazid Karimullah Institute, 2024)
PAUD learning to improve children's fine motor skills. Origami was chosen as a method because it can stimulate fine motor skills development through precise hand movements and eye coordination. This research was conducted at KB Nurul Hilmi Bondowoso. The research approach used is qualitative research, with a descriptive research type. The data collection techniques used were interviews, observation, and documentation. Data analysis techniques include data reduction, data display, and data verification. Based on the results of this research, exploring origami can improve children's fine motor skills. Before starting learning, KB teacher Nurul Hilmi Bondowoso prepared a daily activity plan related to the activities to be carried out, namely improving children's fine motor skills and preparing observation sheets for students' activities. At the learning stage, KB teacher Nurul Hilmi Bondowoso used the demonstration method in classroom learning activities. At the evaluation and assessment stage of early childhood work, teachers use three categories, namely dexterity, neatness, and following the teacher's instructions.